2015
DOI: 10.12659/ajcr.894041
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Melanoma of the Esophagus: A Case Report and Review of the Literature

Abstract: Patient: Male, 67Final Diagnosis: Primary malignant melanoma of esophagusSymptoms: DysphagiaMedication: —Clinical Procedure: Endoscopic biopsySpecialty: Gastroenterology and HepatologyObjective:Challenging differential diagnosisBackground:Primary malignant melanoma of the esophagus (PMME) is a rare cancer with a poor prognosis. It is often difficult to differentiate from non-epithelial malignant tumors, and immunohistochemical staining may be needed to diagnose the condition. The mainstay of treatment is usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The diagnosis of PMME for our patients was made depending upon post-operative pathological examination with immunohistochemical checkup. The majority of the specimens had positive expression of the classic immunomarkers, like MB-45, Melan-A, S100, and vimetin, which is consistent with other reports 6 10 15 16 . However, accurate diagnosis before surgery is difficult even with endoscopic biopsy.…”
Section: Discussionsupporting
confidence: 91%
“…The diagnosis of PMME for our patients was made depending upon post-operative pathological examination with immunohistochemical checkup. The majority of the specimens had positive expression of the classic immunomarkers, like MB-45, Melan-A, S100, and vimetin, which is consistent with other reports 6 10 15 16 . However, accurate diagnosis before surgery is difficult even with endoscopic biopsy.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, although biopsy of malignant melanoma is conventionally not considered to be indicated, there have been no reports of metastasis or dissemination after biopsy, and it has been reported that the presence or absence of biopsy has no effect on the prognosis (3). Therefore, in order to obtain a definitive diagnosis, many reports suggest that a biopsy should be performed when a suspicious lesion is detected by endoscopy (12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%